Understanding psychiatrists' knowledge, attitudes and experiences in identifying and supporting their patients on the autism spectrum: online survey. Issue 3 (May 2019) - Crane, Laura; Davidson, Ian; Prosser, Rachel; Pellicano, Elizabeth
Abstract : Background: Psychiatrists play a critical role in identifying and supporting their patients on the autism spectrum in the UK, yet little is known about their knowledge, attitudes and experiences in this regard. Aims: To understand psychiatrists' experiences of working with autistic individuals, their confidence in making diagnostic/management decisions and the factors that affect such decisions. Method: A total of 172 psychiatrists took part in an online self-report survey. Results: Most psychiatrists reported receiving useful training on autism and were knowledgeable about the condition, particularly those with a personal connection to autism. Higher confidence in working with autistic patients was linked to greater levels of autism knowledge, experience and training. Several systemic and autism-specific factors were highlighted by psychiatrists, which were felt to challenge their ability to provide effective care and support for their patients on the autism spectrum. Conclusions: Psychiatrists' views corroborated previous research with the autism community, highlighting the need to co-design services that are accessible, respectful and person-centred. Declaration of interest: I.D. is the Royal College of Psychiatrists' Autism Champion.